Data access in the ASP.NET 2.0 framework - Walther, Stephen (LiveLessons., 2007)
"Data Access in the ASP.NET 2.0 Framework will show you everything you need to know to start building database-driven web applications using the Microsoft ASP.NET 2.0 framework and the Microsoft Visual Studio 2005 development environment. Your instructor Stephen Walther--honored by Microsoft as both an ASP.NET MVP and 'Software Legend'--guides you through building two fully functional, database-driven applications. Learn at your own pace with video lessons covering every main ASP.NET data access control: GridView, DetailsView, FormView, Repeater, DataList, and SqlDataSource. One step at a time, you'll learn how to build robust data access components, provide graceful error handling, handle user concurrency issues, and much more."--Resource description page